Small Schools in a Big World: Thinking About a Wicked Problem - Corbett, Michael; Tinkham, Jennifer (Alberta Journal of Educational Research, 2015)
The position of small rural schools is precarious in much of rural Canada today. What is to be done about small schools in rural communities which are often experiencing population decline and aging, economic restructuring, and the loss of employment and services? We argue this issue is a classic "wicked" policy problem. Small schools activists have a worldview that is focused on maintaining infrastructure and even community survival, while school boards are mandated to focus on the efficient provision of educational services across wider geographies. Is it even possible to mitigate the predictable conflict and zero-sum games that arise with the decision to close small schools? That is the subject of this paper, which draws on poststructural and actor network theory. We suggest that wicked problems cannot be addressed satisfactorily through formulas and data-driven technical-rational processes. They can only be addressed through flexible, dialogical policy spaces that allow people who have radically different worldviews to create dynamic, bridging conversations. Fundamentally, we argue that what is required are new spaces and modes of governance that are sufficiently networked, open, and flexible to manage the complexity and the mutability of genuinely participatory democracy. De nos jours, la situation des petites écoles rurales est précaire dans beaucoup de milieux ruraux au Canada. Que faire des petites écoles dans les milieux ruraux souvent aux prises avec une population vieillissante et en déclin, une restructuration économique, et une perte d’emplois et de services? Nous soutenons que cette situation est un problème classique de politique « pernicieuse ». Les activistes des petites écoles ont une vision du monde axée sur le maintien de l’infrastructure, voire la survie communautaire, alors que les conseils scolaires sont chargés de miser sur la prestation efficace de services éducationnels sur de plus grandes étendues. Est-il même possible de mitiger le conflit prévisible et les jeux à somme nulle qui découlent de la décision de fermer de petites écoles? Voilà le sujet de cet article, qui puise dans la théorie post-structurale et la théorie du réseau d’acteurs. Nous proposons que les problèmes pernicieux ne peuvent être abordés de façon satisfaisante par les formules et les processus technico-rationnels axés sur les données. Ils ne peuvent être résolus que par des politiques souples et dialogiques qui permettent aux gens avec des visions du monde radicalement différentes de créer des conversations dynamiques qui appuient le rapprochement. Dans le fond, nous militons en faveur de nouveaux espaces et de nouveaux modes de gouvernance qui sont suffisamment réseautés, ouverts et souples pour gérer la complexité et la mutabilité d’une démocratie authentiquement participative.